Antioxidant and Anti-tyrosinase Activities of Nanocream of Resam Leaves (Dicranopteris lineraris) and Jeruk Kunci Fruits Waste (Citrus x microcarpa) Extract - Roanisca, Occa; Hidayat, Rian; Tafdila, Nova Azka (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2025)
Abstract: Premature aging especially among women has become a serious problem that impacts self-confidence. This is caused by exposure to excess ultraviolet radiation, which induces the formation of reactive oxygen species and increases the activity of tyrosinase enzymes in the melanogenesis process. This study examined the antioxidant and anti-tyrosinase capabilities of nanocream formulated with Dicranopteris linearis (resam) leaf and Citrus x microcarpa (jeruk kunci) fruit extracts sourced from Bangka Belitung. A stepwise microwave-assisted extraction process was conducted using three solvents n-hexane, ethyl acetate, and ethanol, with ethanol proving most effective at extracting bioactive compounds (64.97% yield from resam leaves and 21.12% from jeruk kunci). Phytochemical screening showed that ethanol extracts contained the highest levels of active compounds: resam extracts had 179.78 mg GAE/g total phenolics and 90.33 mg QE/g total flavonoids, while jeruk kunci extracts contained 135.65 mg GAE/g phenolics and 72.64 mg QE/g flavonoids. Physical characterization confirmed the nanocream met quality standards specified in Indonesian National Standard SNI 16-4954-1998. Biological testing revealed strong antioxidant properties, with the nanocream achieving IC₅₀ values between 7.34 and 16.36 μg/mL, markedly better than single extracts alone (IC₅₀ 29.58–72.33 μg/mL). The formulation also showed considerable tyrosinase inhibitory activity at IC₅₀ 100.16 μg/mL. The results indicate the potential of resam leaves and jeruk kunci fruits extract nanocream as an innovative natural ingredient-based anti-aging cosmetic preparation. Abstrak: Penuaan dini terutama di kalangan wanita telah menjadi masalah serius yang berdampak pada kepercayaan diri. Hal ini disebabkan oleh paparan radiasi ultraviolet berlebih yang menginduksi pembentukan reactive oxygen species dan meningkatkan aktivitas enzim tirosinase dalam proses melanogenesis. Penelitian ini bertujuan mengembangkan sediaan nanokrim anti-aging dari ekstrak daun resam (Dicranopteris linearis) dan buah jeruk kunci (Citrus x microcarpa) asal Bangka Belitung. Ekstraksi bertingkat dengan metode Microwave Assisted Extraction menggunakan pelarut n-heksana, etil asetat, dan etanol menunjukkan rendemen tertinggi pada ekstrak etanol (64,97% daun Resam; 21,12% Jeruk Kunci). Ekstrak etanol kedua sampel mengandung senyawa fenolik dan flavonoid tertinggi dengan kadar fenolik total 179,78 mg GAE/g (daun resam) dan 135,65 mg GAE/g (limbah buah jeruk kunci) serta kadar flavonoid total 90,33 mg EK/g (daun resam) dan 72,64 mg QE/g (limbah buah jeruk kunci). Formulasi nanokrim menunjukkan karakteristik fisik memenuhi standar SNI 164954-1998. Sediaan nanokrim menunjukkan aktivitas antioksidan sangat kuat (IC50 7,34-16,36 μg/mL) dengan peningkatan signifikan dibandingkan ekstrak tunggal (IC50 29,58-72,33 μg/mL) serta aktivitas anti-tirosinase kategori kuat (IC50 100,16 μg/mL) melalui penghambatan enzim tirosinase. Hasil penelitian mengindikasikan potensi nanokrim ekstrak daun resam dan limbah buah jeruk kunci sebagai inovasi sediaan kosmetik anti-aging berbasis bahan alam.